2007
DOI: 10.1103/physrevb.75.014415
|View full text |Cite
|
Sign up to set email alerts
|

Memory effect and spin-glass-like behavior in Co-Ag granular films

Abstract: The memory effect was clearly observed in dc-sputtered metallic, magnetic Co-Ag granular films, which indicates the existence of a spin-glass-like phase at low temperatures. However, the memory effect diminished dramatically after the films were annealed at 300°C for 1 h. It was also found that the memory effect weakened gradually with increasing volume fraction of magnetic clusters. The experimental results indicate that the dipolar interaction is not the major origin for the formation of low-temperature spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 48 publications
8
53
2
Order By: Relevance
“…21,22 This corroborates our picture where it is the clusters themselves that facilitate correlation over longer distances. The difference in magnetic behavior of the two samples of equal concentration shown in Figs.…”
Section: ͑3͒supporting
confidence: 79%
See 1 more Smart Citation
“…21,22 This corroborates our picture where it is the clusters themselves that facilitate correlation over longer distances. The difference in magnetic behavior of the two samples of equal concentration shown in Figs.…”
Section: ͑3͒supporting
confidence: 79%
“…Deviations from this simple formalism are due to intra-or intercluster interactions ͑neglecting the quantization of magnetic moment orientation͒ and manifest themselves as "flat-top" GMR curves in postannealed samples. 8,19,20 Magnetic ordering and spin-glass-like behavior have also been observed in rather dilute postannealed granular samples 21,22 but the strongly inhomogeneous concentration and large size distributions make an unambiguous interpretation difficult. We have developed an experimental setup that allows the fabrication of embedded magnetic nanostructures through cluster assembly in a nonmagnetic metallic matrix.…”
Section: Introductionmentioning
confidence: 99%
“…35 The aging and memory effects are the two aspects that have been studied extensively in recent years, however mostly for the case of ferromagnetic particles. [7][8][9]16,[18][19][20][21][22][23][24][25][26][27] In this paper our aim is to investigate these effects for collection of a few antiferromagnetic nanoparticles (AFNs) which has received relatively lesser attention.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31] It has been shown that the dipolar interaction plays a very important role for the magnetic properties for SPM ensembles with a sufficiently short distance between granules. Such a type of magnetic material was called the "interacting superparamagnets."…”
Section: Discussionmentioning
confidence: 99%